Synthesis and Application of Reactive Fluorescent Brightening Agents on UV Irradiated Cotton Fabric - Misbah; Ahmad Bhatti, Ijaz; Ahmad, Zahra; Iqbal, Munawar (Asian Journal of Chemistry, 2015)
In present study stilbene based optical brightening agents were synthesized and applied to UV irradiated cotton fiber. Synthesis comprised the condensation between 4,4-diaminostilbene-2,2-disulfonic acid followed by condensation with other substituents such as diethanolmine, metanilic acid, vinyl sulfone paraester and ester prepared by esterification of diethanolamine separately. The synthesized brighteners were applied on UV irradiated and un-irradiated cotton fabric. The UV radiation intensity of 180 watt for 1 h was used. Absorption spectra of these brighteners was recorded using double beam spectrophotometer CECIL CE 7200/Data stream software. CIE whiteness of fabric samples was recorded using spectra flash SF 600/UK. After optical brightening agent’s application, the cotton fabric samples were also tested for washing, chlorine and light fastness properties. CIE whiteness was noted to be significantly higher in case of irradiation versus unirradiated samples and fastness properties did not changed. On the basis of results, the application of brightening agent on UV irradiated cotton is suggested for the enhancement of cotton fabric properties to enhance the whiteness.